A controlled alkaline treatment of Al-SBA-15: a facile route to adjust the chemical composition and synthesize an ordered mesoporous carbon material, CMK-3, possessing strong pressure resistant capability. (5th July 2017) - Lin, Sen; Liu, Ruiyun; Li, Niping; Guo, Peng; Shi, Lei
Abstract : Alkaline-treated Al-SBA-15 exhibits excellent catalytic performance in the LDPE degradation reaction and its replica, CMK-3, has excellent structural stability. Abstract : The effect of an alkaline treatment on the mesoporous material Al-SBA-15 was investigated using powder X-ray diffraction (XRD), inductively coupled plasma (ICP) analysis, mid-infrared spectroscopy (IR), N2 sorption isotherm measurements, transmission electron microscopy (TEM), scanning electron microscopy (SEM), solid state 27 Al MAS NMR analysis, and structural replicating technology. It was observed that elemental Si could be readily extracted from wall structures, and the Al-rich surface that was consequently exposed protected the uniform hexagonal arrays. The extracted substances rapidly accumulate inside the Al-SBA-15 mesopores and continuously dissolve and migrate into the alkaline solution upon a prolonged treatment time. Therefore, alkaline-treated Al-SBA-15 exhibits a larger pore size and a thinner wall than that before treatment. Due to its Al-rich surface and highly-open mesostructure, alkaline-treated Al-SBA-15 exhibits excellent catalytic performance in a low density polyethylene (LDPE) catalytic degradation reaction. The temperature corresponding to the maximum degradation rate was measured to be ∼10 K lower than that in raw Al-SBA-15. More importantly, the secondary-scale mesopores inside the Al-SBA-15 walls were remarkably expanded, allowing efficient penetration of the carbon precursor. Its structural replica, CMK-3, has a highly ordered mesostructure, which is attributed to the formation of enhanced carbon sticks that connect the primary carbon rods. For the same reason, CMK-3 templated from alkaline-treated Al-SBA-15 exhibits a strong pressure resistant capability. The reduction in the surface area and pore volume after high-pressure treatment were calculated to be as low as 4.5% and 3.0%, respectively.